THE IMPACT OF CHANGES IN ELECTRONIC MEDICAL RECORDS IMPLEMENTATION ON PATIENT SATISFACTION (EMPIRICAL STUDY IN THE OUTPATIENT CLINIC AT PERSADA HOSPITAL MALANG). (Proceedings OPTIMAL, 2026)
Hospitals are required to improve the quality of healthcare services by utilizing current technological developments to compete effectively (Ministry of Health, 2020). Digital transformation in healthcare systems has been a global agenda recommended by the World Health Organization (WHO) since the early 2000s, including the implementation of Electronic Medical Records (EMRE) as a strategy to improve service quality, operational efficiency, and patient safety (Ludwick and Doucette, 2009). This study used a quantitative survey approach to analyze the effect of Electronic Medical Record Implementation on Patient Satisfaction in the outpatient clinic at Persada Hospital Malang. The sample consisted of 110 respondents. Sampling was adjusted to meet exclusion and inclusion criteria using a simple random sampling technique. The data collection tool was a closed-ended questionnaire. Data analysis was statistically tested using the Chi-Square Test to determine the effect of changes in Electronic Medical Record Implementation on patient satisfaction with a 95% confidence level or a significance level (α = 0.05). The bivariate analysis results indicate a high level of patient satisfaction in the outpatient clinic, supported by five factors: tangibles, reliability, responsiveness, assurance, and empathy. The study concluded that changes in the implementation of Electronic Medical Records directly impacted patient satisfaction in the outpatient clinic at Persada Hospital Malang.